Leveraging strategic intuition to reach firm performance: the role of entrepreneurial agility and environmental dynamism - Zulganef Zulganef; Sri Astuti Pratminingsih; Andri Rianawati (Jurnal Siasat Bisnis, 2023)
Purpose – This study was carried out to analyze the influence of strategic intuition on firm performance through the role of entrepreneurial agility as mediator and environmental dynamism as a moderator. Design/methodology/approach – This study was conducted using quantitative approach. The number of samples in this study was 280 SMEs actors in Bandung, West Java. The data in this study was collected by distributing questionnaire to the respondents. The data obtained was then processed and analyzed using Structural Equation Modelling with Partial Least Square, using Smart-PLS software. Findings – The findings of this study proved that: (1) Strategic intuition positively influenced firm performance; (2) Strategic intuition positively influenced entrepreneurial agility; (3) Entrepreneurial agility positively influenced firm performance; (4) Environmental dynamism negatively moderated the relationship between strategic intuition and entrepreneurial agility; and (5) Environmental dynamism negatively moderated the relationship between entrepreneurial agility and firm performance. Research limitations/implications – This study attempted to understand the concept of entrepreneurship in a dynamic environment using entrepreneurial agility as one of the constructs, and linked it with firm performance. However, this study had not yet differed the respondent based on their business type. Future studies can analyze further about the phenomenon that occurred within different kind of business using different level of analysis, such as comparing the condition within and between group of entrepreneurs. Practical implications – This study provided contributions to SMEs actors in Bandung, as it can be a consideration for the way they run their business within a volatile business environment. Originality/value – This study was giving a deep understanding of strategic intuition on firm performance with the mediation role of entrepreneurial dan moderator role of environmental dynamism in the scope of SMEs.